Enhancing critical thinking through differentiated instruction in primary education: A systematic literature review - Waode Sitti Fatimah; Ikhlasul Ardi Nugroho; Unik Ambar Wati; Fery Muhamad Firdaus; Muhammad Ilham; Syifa Zia Muharni; Sulaiman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The cultivation of critical thinking skills is a central aim of modern pedagogy. This study systematically synthesizes empirical evidence on the implementation of differentiated instruction and its contribution to developing critical thinking skills in elementary students, as examined through research designs, implementation strategies, and learning outcomes. A Systematic Literature Review (SLR) approach, reported in accordance with PRISMA 2020 guidelines, was employed. The literature search was conducted from May 15–20, 2024, using the Scopus, ERIC, and Google Scholar databases via Publish or Perish. Articles were selected according to the inclusion criteria, and the methodological quality was assessed using an adapted Mixed Methods Appraisal Tool (MMAT). Data synthesis was performed using a narrative-thematic approach. A total of 12 empirical studies published between 2020 and 2024 were analyzed, with research contexts predominantly from Indonesian elementary schools and complemented by several international studies. The review indicates that the studies primarily utilized descriptive qualitative, classroom action research, and quasi-experimental designs. Differentiated instruction was implemented according to Tomlinson's framework, incorporating differentiation across content, process, and product, and was frequently integrated with Problem-Based Learning and Project-Based Learning models. The findings demonstrate improvements in students' critical thinking skills, particularly in analytical reasoning, decision-making, and reflection, as well as enhanced motivation and learning engagement. Future research is recommended to explore the long-term impact of technology and its role in optimizing differentiated instruction.